Pendekatan Hukum Pidana dalam Menangani Penyeludupan Barang Ilegal di Indonesia: Analisis Mendalam dan Studi Komparatif dengan Kebijakan serta Praktik Penegakan Hukum di Negara-Negara Anggota Asean - Feny Windiyastuti; Ricky Virgiawan; Hamzah Robbani (Decisio: Jurnal Ilmiah Hukum, 2024)
This study investigates Indonesia's criminal law approach in addressing the significant challenge of illegal goods smuggling, impacting national security and regional-global stability, encompassing issues like illegal fishing, piracy, marine pollution, terrorism, and drug abuse. Employing comparative and qualitative analysis methods, the research compares Indonesia's practices with those of ASEAN countries, using primary and secondary legal data. The findings highlight the need for enhanced inter-agency coordination, infrastructure development, and international cooperation, recommending strengthening regional collaboration, improving prevention and enforcement, and risk mitigation. This study contributes to national and regional security policies, focusing on the management of illegal goods smuggling in ASEAN.